University Students’ Perspectives on Lecturer’s Digital Class Organization in Teaching ESP amid Covid-19 Pandemic - Ramadhani, Reski; Aulawi, Hilmi; Ikhwana, Andri (Elsya : Journal of English Language Studies, 2022)
This study aims to investigate students’ perspectives on digital classroom organization implemented during online learning in teaching ESP in the context of higher education level at Garut Technology of Institute. To evaluate the organization of digital class utilization in language learning and determine the barriers and opportunities during the process, a mixed-method design with a close-ended questionnaire and an open-ended questionnaire was employed to reveal the students’ perspectives. 90 informatics engineering students studying English for Specific Purposes (ESP) were recruited in this study. The findings revealed that the students positively argued that their lecturer is capable of organizing and implementing various digital platforms during online learning. Most of the students are still motivated and engaged in learning even though it is conducted virtually. Besides, the platforms used by the lecturer synchronously and asynchronously are deemed to be effectively able to replace the face-to-face offline media since it keeps the lecturer and students interacting with one another. Some of the barriers come from the stability of internet access, students’ data, available devices, and particular technical issues. The implications suggest that both lecturers and students should prepare to adopt the digital classroom since it will be the new direction in language teaching.